Pengaruh Human Capital, Keunggulan Bersaing, dan Orientasi Kewirausahaan Terhadap Kinerja Organisasi UMKM di Sumatera Barat - Wael, Zahra Rahmatika; M., Herawati (Jurnal Eksplorasi Akuntansi, 2025)
This “study aims to examine: (1) whether human capital influences the organizational performance of MSMEs in West Sumatra; (2) whether competitive advantage affects their organizational performance; and (3) whether entrepreneurial orientation has an impact on MSME organizational performance in the region. The population consists of Micro, Small, and Medium Enterprises located in West Sumatra. A total of 100 respondents were selected from MSMEs registered with the Department of Cooperatives and SMEs of West Sumatra or through http://umkm.depkop.go.id. The study employed a probability sampling method using simple random sampling and incidental sampling techniques. The findings reveal that: (1) human capital significantly contributes to the organizational performance of MSMEs; (2) competitive advantage has a positive effect on their performance; and (3) entrepreneurial orientation does not significantly influence MSME organizational performance in West Sumatra.” The implication of this study is to provide recommendations for improving SMEs in order to enhance their” performance.